"Serving two masters" - academics' perspectives on working at an offshore campus in Malaysia - Dobos, Katalin (Routledge Publishing, Taylor & Francis Group, 2011)
This paper explores the effects of the internationalisation of higher education on the working lives of academics at an offshore campus in eastern Malaysia. Using the interpretivist paradigm and grounded theory methods it investigates their perspectives on various themes as those emerge during a series of interviews. These emerging themes are: “Professional Practice”, “Communication”, “Quality Assurance” and “Curriculum Issues”. These themes are interrelated, are tied together with the anchor theme of “serving two masters” and expose important areas that need to be monitored by both the offshore and Australian partners in order to ensure the quality and success of their cooperation in the long term.